Relationship between stress, anxiety and family environment in Turkish married individuals. - Zubaroğlu Yanardağ, Melek; Çay, Murat; Özden, Seda Attepe (Journal of Human Behavior in the Social Environment)
The purpose of this study is to determine how the family environment affects the stress and anxiety levels of married women and men living in the city center of Antalya. The study was defined as a descriptive quantitative research and 455 married individuals attended. Between 20 February and 20 April 2022, data were gathered at parks, bazaars, markets, streets, restaurants, and private workplaces in the Antalya city center's Kepez, Konyaaltı, and Muratpaşa districts. The findings showed that there was a positive and weak correlation (r = 0.306) between stress and anxiety that the participants felt. The family environment had a weak and negative correlation with anxiety. The increase in the perceptions of the participants about the anxiety state elevated their stress levels (R2=.093). The increased perceptions of the family environment also decreased anxiety levels (R2=.052). It can be asserted that the family environment had a direct effect on the anxiety level of individuals and an indirect impact on their stress levels. Psychosocial interventions offer important and valuable insight for helping married individuals reduce their anxiety and stress levels.